Радионуклиды в рыбе Зоны отчуждения Чернобыльской АЭС - Гудков, Д.И.; Каглян, А. Е.; Назаров, А.Б.; Кленус, В. Г. (Видавничий дім "Академперіодика" НАН України, 2007)
The results of researches of the spicespecificity, accumulation dynamics, and distribution of 90Sr, 137Cs, and transuranic elements in fish of the Chernobyl NPP exclusion zone are analyzed. For fish of lakes of the left-bank floodplain of the Pripyat River, the increase of the specific activity of 90Sr is registered, which is presumably connected to the dynamics of physico-chemical forms of the radionuclide in soils and their wash out in water basins from the catchment territory. Now about 90% of the internal dose rate of fish from closed aquatic ecosystems within the Chernobyl NPP exclusion zone are caused by the 90Sr incorporation.